A study on the introduction of LPG as fuel for vehicles in Malaysia - 366933 Ahmad Subhan Ridzuan; Mohd. Fadil Abdul Wahab (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan Kimia (Gas)) - Universiti Teknologi Malaysia, 2008